Problem-Based Interactive Media to Improve Students’ Critical Thinking Skills in Social Studies - Laely Nafi'atus Shokhah; Djono; Sudiyanto (Universitas Pendidikan Ganesha, 2025)
Ninth-grade Social Studies learning has not been fully effective due to the lack of varied instructional methods and the absence of adequate media to enhance students’ critical thinking skills at MTs in Semarang Regency. This study aims to develop interactive learning media based on the Canva and Heyzine applications to improve students’ critical thinking skills. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection methods included interviews, observation, and questionnaires. The data collection instruments comprised Likert-scale (1–5) questionnaires and multiple-choice tests. Data were analyzed using descriptive analysis techniques. The results showed that the interactive media based on Canva and Heyzine applications were validated by experts, with 82.95% for media expert validation and 89.73% for content expert validation, while trials with students achieved an average score of 93.58%. Therefore, the problem-based interactive media on the topic of globalization is deemed suitable for use in learning at MTs in Semarang Regency. Furthermore, the use of this media has proven effective in enhancing students’ critical thinking skills.